Superficial CD34‐positive fibroblastic tumour: a clinicopathological and immunohistochemical study of an additional series. Issue 3 (22nd November 2016) - Lao, I Weng; Yu, Lin; Wang, Jian
Abstract : Aims: To describe an additional series of superficial CD34‐positive fibroblastic tumour, a newly described neoplasm, in order to enhance the recognition of an emerging novel entity. Methods and results: The clinicopathological features and immunophenotypes of 11 cases of superficial CD34‐positive fibroblastic tumour were studied. There were eight males and three females, with a median age of 36 years. Tumours occurred in the thigh ( n = 4), buttock ( n = 3), shoulder ( n = 2), upper arm ( n = 1), and waist ( n = 1). Histologically, all tumours were characterized by relative circumscription, pleomorphic spindled to polygonal cells with variably enlarged bizarre‐appearing cells, intranuclear cytoplasmic pseudoinclusions, and extremely low mitotic activity. Immunohistochemically, neoplastic cells showed diffuse and strong expression of CD34 and focal staining of cytokeratin. Follow‐up thus far has revealed an indolent clinical behaviour. Conclusions: Superficial CD34‐positive fibroblastic tumour represents a new member of the family of cutaneous CD34‐positive spindle‐cell tumours. Familiarity with its clinicopathological characteristics is helpful in avoiding confusion with a variety of cutaneous mesenchymal tumours with overlapping features.